Variation in Soil Methane Fluxes and Comparison between Two Forests in China - Wei, Hua; Peng, Changhui; Liu, Shirong; Liu, Xiaojing; Li, Peng; Song, Hanxiong; Yuan, Minshu; Wang, Meng (Forests, 2018)
Methane (CH4) is a vital greenhouse gas with a 28-fold higher global warming potential than carbon dioxide when considering a molar basis for the time horizon of 100 years. Here, we investigated the variation of soil CH4 fluxes, soil physiochemical properties, and CH4-related bacteria community composition of two forests in China. We measured CH4 fluxes using static chambers and analyzed soil bacterial communities using next-generation high-throughput sequencing in a temperate broad-leaved deciduous forest at Baotianman Nature Reserve (TBDF-BTM) and a tropical rainforest at Jianfengling National Natural Reserve (TRF-JFL). Our results showed that the soils from both sites were CH4 sinks. Significant variation in soil CH4 fluxes was found at TBDF-BTM exclusively, while no seasonal variation in the CH4 uptake was observed at TRF-JFL. The CH4 fluxes at TBDF-BTM were substantially higher than those at TRF-JFL during all seasons. One genus of methanotrophs and three genera of methylotrophs were detected at both sites, though they had no direct relationship with soil CH4 fluxes. Water-filled pore space and soil total carbon content are the main factors controlling the soil CH4 fluxes at TBDF-BTM. At TRF-JFL, the soil CH4 fluxes showed no significant correlations with any of the soil properties. This study improves our understanding of soil CH4 fluxes and their influencing factors in forests in different climatic zones and provides a reference for future investigation of forest soil CH4 fluxes, the forest ecosystem carbon cycle, and the forest CH4 model.

Contrasting Soil Bacterial Community, Diversity, and Function in Two Forests in China - Wei, Hua; Peng, Changhui; Yang, Bin; Song, Hanxiong; Li, Quan; Jiang, Lin; Wei, Gang; Wang, Kefeng; Wang, Hui; Liu, Shirong; Liu, Xiaojing; Chen, Dexiang; et al. (Frontiers in Microbiology, 2018)